Dinamika dan Transformasi Implementasi Evaluasi Pendidikan pada Masa Darurat Covid-19 - Anuraga Jayanegara; Ismail Marzuki (Universitas Muhammadiyah Tangerang, 2022)
The emergence of the Covid-19 pandemic on a global scale has caused major impacts on various sectors, including the education sector. In order to reduce the spread of Covid-19, many countries have implemented learning from home, distance learning or e-learning. Several online platforms that are widely used as learning media include Microsoft Teams, Google Classroom, and Canvas and Blackboard, which allow teachers to create learning development programs. These online platforms have various features including chat, video meetings and file storage that keep classes organized and easy to learn. Such change in the learning methods requires the adjustment of educational evaluation system or learning assessment towards the online tests or other forms of distance assessment. The main problem with online evaluation is that the exams are performed without the physical presence of both students and teachers As a consequence, verification of the examinees and the potential for cheating among the students have appeared as major obstacles during the online learning assessment. Another obstacle that arises in online exams is related to facilities such as hardware (laptops, androids, tablets, etc.), software as well as the stable internet connection for all students.